REVIEW - PENGEMBANGAN KURKUMIN DAN ANDROGRAFOLIDA UNTUK SEDIAAN PARENTERAL - Mansauda, Karlah; Rumondor, Erladys Melindah (PHARMACON, 2020)
ABSTRACTCurcuma longa Linn (Kunyit) and Andrographis paniculata (Burm.f.) Nees (Sambiloto) are some examples of plants that grown in Indonesia that provides many health benefits with their isolated coumpound Curcumin and Andrographolide, respectively. However, due to their low water-solubility, low stability, rapid metabolism, poor absorption, and degradation during processing or within the gastrointestinal tract and alkaline conditions therefor reduces its oral bioavailability and consequently decreasing its development as a therapeutic drugs via oral. The advantage of parenteral route of administration including reduced toxicity, improved drug solubility and stability, prolonged circulation time, and enhanced tissue penetration. This review summarizes and discusses published journals on the key development on parenteral delivery system of curcumin and andrographolide as active ingredients. Keywords : Curcumin, Andrographolide, Parenteral ABSTRAKCurcuma longa Linn (Kunyit) dan Andrographis paniculata (Burm.f.) Nees (Sambiloto) adalah beberapa contoh tanaman yang tumbuh di Indonesia yang memberikan banyak manfaat kesehatan dengan senyawa yang terkandung didalamnya seperti Kurkumin dan Andrografolida. Namun karena sifatnya sukar larut dalam air, stabilitas rendah, metabolisme yang cepat, susah diabsorbsi, dan terdegradasi dalam asam lambung dan kondisi alkali, akibatnya menurunkan bioavailabilitas oralnya dan mengurangi manfaatnya. Pemberian secara parenteral adalah rute yang memiliki keuntungan termasuk mengurangi toksisitas, meningkatkan kelarutan obat dan stabilitas, memperpanjang waktu sirskulasi, dan peningkatan penetrasi jaringan. Ulasan ini merangkum dan membahas jurnal pada mengenai pengembangan sistem penghantaran secara parenteral dengan kurkumin dan andrografolida sebagai senyawa aktifnya. Kata Kunci : Kurkumin, Andrografolida, Parenteral